Representativeness of the European social partner organisations - Adam, Georg,Kerckhofs, Peter,Cojocariu, Victoria (Eurofound, 2023)
This study provides information allowing for an assessment of the representativeness of the actors involved in the European sectoral social dialogue committee for the professional football sector. Their relative representativeness legitimises their right to be consulted, their role and effective participation in the European sectoral social dialogue and their capacity to negotiate agreements. The aim of Eurofound's studies on representativeness is to identify the relevant national and European social partner organisations in the field of industrial relations in the EU Member States. This study identifies Fifpro - representing employees - and European Leagues and ECA - representing employers - as the representative European-level social partner organisations in the professional football sector.
10.2806/487052
Keywords: Graue Literatur; Amtliche Publikation; Representativeness; Collective bargaining; Industrial relations and social dialogue; Industrial relations; Social dialogue; Social partners; professional sport; sports body; labour relations; EU Member State; research report